중국 지방정부기업화와 도시 공간재편 - 김현석; Kim Hyeonsuk (중국연구, 2017)
Since the reform and opening, China has been pursuing various aspects such as social, economic, and politics continuously, and the role of local government has been transformed into a profitable enterprise in the midst of changes in globalization, decentralization, marketization policy and development environment. At the same time, the construction of new cities in the rapid urbanization wave is rapidly increasing, and the local government has a great influence on the urban space production and reorganization due to its characteristics of enterprise as a new city construction subject. This paper analyzes the mechanism of Local Government Entrepreneuralism on the urban space production and reorganization, starting from the transition of the capital accumulation to the city and the local government enterpriseization. The formation of space in China was driven by the local government, which was driven by the power of capital accumulation and commercialized. In order to overcome the contradictions of capital accumulation and spatial inclusion, new spatial organization is being achieved through the incorporation of marketization, decentralization, and global economy. The new Spatial Configuration just made the city a reality of capital accumulation. The formation of urban space in China is the result of the transformation of the capital accumulation system, and the growth federation (local government enterpriseization) led to urban space production and Spatial Configuration.